Government Buildings, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
Exterior view of the government building the Red House which is the seat of parliament in Trinidad and Tobago. Some persons are seen walking/riding on Abercromby Street which runs alongside the east side of the building.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Historic buildings--Trinidad and Tobago; Public buildings--Trinidad and Tobago; 1922; Architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Red House, The